In‐Hospital mortality varies by procedure type among cirrhosis surgery admissions. (17th June 2019) - Mahmud, Nadim; Fricker, Zachary; Serper, Marina; Kaplan, David E.; Rothstein, Kenneth D.; Goldberg, David S.
Abstract: Background: Patients with cirrhosis have increased peri‐operative mortality risk relative to non‐cirrhotic patients, however, the impact of surgical procedure category on this risk is poorly understood. Methods: We performed a retrospective cohort study of cirrhosis surgery admissions using the National Inpatient Sample between 2012 and 2014 to estimate the adjusted odds of in‐hospital mortality by surgical procedure category. Results: In‐hospital mortality differed by surgical procedure category. Relative to major orthopedic surgeries, major abdominal surgeries had the highest odds of in‐hospital mortality (odds ratio [OR] 8.27, 95% confidence interval [CI] 5.96‐11.49), followed by major cardiovascular surgeries (OR 3.45, 95% CI 2.33‐5.09). There was also a significant interaction term, whereby elective/non‐elective admission status impacted in‐hospital mortality risk differently for each surgical procedure category ( P < 0.001). Conclusion: In‐hospital mortality varies substantially by surgical procedure type. Accounting for procedure type in models may improve risk prediction for peri‐operative mortality in patients with cirrhosis.